(untitled) (Damascus University Journal for engineering sciences, 2023)
The myth is a guide to the past of civilizations, and it is an attempt to understand the world with its major and cosmic issues, which in turn reach the later generations thoughts.The myth is the product of the human imagination through the ages, so it is a cultural and social phenomenon that has been linked to the beliefs of peoples, that is why it is sacred, but a dispute occurred through ages between those dealing with the concept of myth some are accepting it and another rejecting it, and in many cases the concept of myth was confused with other terms such as the tale and fable, therefore the research will attempt to develop a definition that partially surrounds the concept, through a set of theoretical approaches that showe the views of specialists from philosophers, scientists, writers, and historians of religions, and then analyzing them, and through the analysis of these studies the research will clarify the difference between myth as a concept and other stories and what its relation to history and religion.After that, the research clarifies the role of myth in the artistic product and the architectural work together, because there is no myth without art and architecture and through them myth is able to show its beliefs and its symbolic system, therefore the research presents some of theoretical studies that deal with the relationship betwwen myth architecture and art, in an attempt to reach a definition of the architectural and artistic work that deals with the myth.Then the research takes the reader on a historical tour reviewing the changes that affected the way myth was dealt with in artistic and architectural work through different ages from ancient to contemporary, to conclude the research with a general results that put a set of characteristics which express the myth in architectural work, And the specifications of the architect who deals with the